PENGARUH EFEKTIVITAS DAN EFISIENSI PENYALURAN KREDIT USAHA RAKYAT (KUR) BSI TERHADAP PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI BANK SYARIAH INDONESIA DI BSI KCP MUARA BULIAN - Putri Wulandari; Ansori Ansori; Raden Hebat Kurnia (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The research in this thesis is motivated by Bank Syariah Indonesia (BSI) effectiveness and efficiency in distributing KUR applying sharia principles is expected to provide convenience for MSMEs, especially Muslims. It is expected that the contribution of BSI KCP Muara Bulian in increasing the effectiveness and efficiency of KUR distribution, so as to have a greater impact on the development of MSMEs in the region. The research method used is a quantitative method with a survey approach. The population used in this study were MSMEs using KUR in 2022-2023 at BSI KCP Muara Bulian using the Slovin formula, a sample of 75 respondents was obtained, 25 respondents for the trial and 50 were used as a test of the research instrument. The data collection techniques used by the researcher were Observation, Interviews and Questionnaires. The data obtained in this study were analyzed using multiple linear regression analysis with the SPSS version 20 program.